Upaya Peningkatan Kemampuan Numerasi Siswa Menggunakan Metode Math War Berbasis Kearifan Lokal - Putri Milenia; Olvi Safianti; Nurul Azizah Huril Maula; Prima Aprillianti; Risma Imannia; Roni Rodiyana; Muhammad Haris Zunaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Math War method is a learning approach based on multiplication card games designed to help students improve their focus and solve basic multiplication problems. At SDN Jajartunggal 1, numeracy skills among second-grade students were found to be low, as indicated by the results of a diagnostic assessment. To address this issue, the Math War method was implemented with the integration of Surabaya's local cultural wisdom. This study aims to enhance the numeracy skills of 28 second-grade students using this culturally adapted method. The research employed a Classroom Action Research (CAR) model developed by Kemmis and McTaggart, consisting of four stages: planning, action, observation, and reflection. The study was conducted over three cycles, using written tests as the main instrument. The results showed improvement in student learning outcomes: 64.3% mastery in Cycle I, 71.4% in Cycle II, and 78.6% in Cycle III. This met the success indicator, which required at least 75% of students to achieve the Minimum Mastery Criteria (KKM). Therefore, the Math War method, enriched with Surabaya’s local wisdom, proved effective in improving students’ numeracy skills.